A note of caution on CJEU databases - Michal Ovádek (European Law Open, 2024)
The purpose of this short research note is to draw attention to two major pitfalls of working with databases of decisions of the Court of Justice of the European Union. The first one is technical in nature and relates to the discrepant coverage of the Curia and Eur-Lex databases. The second one is linguistic in nature and relates to the fact that most scholars using these databases work in English. New work on this front is capable of addressing the first issue but a change to research practices would be required to address the second.